Isyarat Sufistik Dalam Penafsiran Surat Al-Ankabut : 41 Kajian Tafsir Ruh Al – Ma’ani - Annisa Eka; Septiawadi; Ahmad Muttaqin (AL-MUTSLA, 2025)
This study is motivated by the need to explore the spiritual dimension in Qur’anic interpretation, which is often overlooked in purely rational or textual approaches. Surah Al-‘Ankabut verse 41 contains the parable of the spider’s house, which many commentators, including Al-Alusi in Ruh al-Ma‘ani, interpret as a symbol of human weakness when relying on anything other than Allah. The purpose of this research is to reveal the Sufistic indications contained in Al-Alusi’s interpretation of this verse and to understand how spiritual values are articulated through his Sufi exegetical approach. This research employs a qualitative method with a library research design and content analysis of the Ruh al-Ma‘ani text. The findings show that Al-Alusi interprets the parable of the spider’s house not only as a rational symbol of fragile faith but also as a Sufistic sign of the transience of the world and the necessity of tawhid as the foundation of human spirituality. Through his Sufi approach, Al-Alusi emphasizes the inner meaning of the verse, guiding humans to detach from worldly dependencies and to surrender fully to Allah. These findings are relevant to modern contexts, particularly in understanding contemporary practices of tawassul, where Al-Alusi’s sufistic insights provide boundaries that define tawassul as merely a means to approach Allah and warn against deviations that occur when intermediaries become objects of spiritual dependence beyond the principles of tawhid. Thus, Al-Alusi’s sufistic exegesis not only enriches the interpretation of the verse but also offers an ethical perspective for preserving the purity of tawhid and addressing modern issues of materialism and spiritual crisis.Abstrak: Penelitian ini dilatarbelakangi oleh kebutuhan untuk menggali dimensi spiritual dalam penafsiran Al-Qur’an yang sering sekali terabaikan dalam pendekatan rasional dan tekstual semata. Surat Al-‘Ankabut ayat 41 memuat perumpamaan tentang rumah laba-laba yang oleh para mufasir, termasuk Al-Alusi dalam Ruh al-Ma‘ani, dimaknai sebagai simbol kelemahan ketergantungan manusia kepada selain Allah. Tujuan penelitian ini adalah untuk mengungkap isyarat sufistik yang terkandung dalam penafsiran ayat tersebut serta memahami bagaimana nilai-nilai spiritual diartikulasikan melalui pendekatan tafsir sufistik Al-Alusi. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka dan analisis isi terhadap teks tafsir Ruh al-Ma‘ani. Hasil penelitian menunjukkan bahwa Al-Alusi menafsirkan perumpamaan rumah laba-laba tidak hanya sebagai simbol rasional tentang kerapuhan iman, tetapi juga sebagai isyarat sufistik tentang kefanaan dunia dan pentingnya tauhid sebagai fondasi spiritual manusia. Melalui pendekatan sufistiknya, Al-Alusi menekankan makna batiniah dari ayat yang mengarahkan manusia untuk melepaskan ketergantungan pada selain Allah dan berserah diri sepenuhnya kepada-Nya. Temuan ini relevan dengan konteks modern, terutama dalam melihat praktik tawasul masa kini, di mana nilai sufistik Al-Alusi memberikan batasan bahwa tawasul hanya berfungsi sebagai wasilah menuju Allah dan dapat menyimpang ketika perantara dijadikan objek ketergantungan spiritual yang melampaui prinsip tauhid. Dengan demikian, tafsir sufistik Al-Alusi tidak hanya memperkaya pemahaman terhadap ayat, tetapi juga menawarkan perspektif etis dalam menjaga kemurnian tauhid serta menghadirkan solusi atas problem materialisme dan krisis spiritual dalam kehidupan kontemporer.